Federal Tax Research, 12th Edition - Roby Sawyers (Cengage Learning, 2020)
Provide a thorough discussion of today's tax practices and ethics as your students study primary and secondary sources of tax law and current IRS practices and procedures with Sawyers/Gill's FEDERAL TAX RESEARCH, 12E. This step-by-step approach focuses on hands-on tax research practices while emphasizing the latest versions of today's most popular online tax research tools, including Thomson Reuters Checkpoint, CCH IntelliConnect and BNA Bloomberg. A searchable Research Case Matrix makes it easy to integrate the latest research cases to challenge students' thinking. Significant updates address ethical challenges in taxation today, qualified business income deductions and other legislative changes enacted by the Tax Cuts and Jobs Act of 2017 as well as how Congress enacts technical changes. This edition focuses on key research skills, problem-solving and communication skills most important for today's workplace as students gain an understanding of the most important elements of today's federal tax law.